Inhibitory Factor and Matrix Metalloproteinases Expression in Rats With Myocardial Infarction. (1st September 2022) - Yu, Hui-Zhen; Zheng, Xi; Lu, Li-Hong; Gao, Jie; Pan, Wei; Zhu, Peng-Li; Yu, Peng
Abstract: Background: To investigate the effect of tissue kallikrein 1 (TK-1) overexpression on cardiac remodeling and myocardial expression of macrophage migration inhibitory factor (MIF) and matrix metalloproteinases (MMP) in myocardial infarction (MI) rats. Methods: MI was induced by ligating left anterior descending arteries of Sprague-Dawley (SD) rats. Fifty-five SD rats were divided into sham operation, MI, MI + control adenovirus type 5 (Ad5), and MI + Ad5-TK-1 groups ( n = 10–15 per group). Parameters of cardiac function were obtained by cardiac catheterization. Infarct area and infiltration of inflammatory cells were determined by Masson staining and hematoxylin and eosin staining, respectively. Angiogenesis was detected by CD34 immunofluorescence intensity. Transfection with recombinant adenovirus and TK-1 expression in myocardium of rats were verified by immunofluorescence and western blot. MIF, MMP-2, and MMP-9 expression was determined by western blot. Results: Compared with sham controls, rats in MI and control virus groups showed a significantly reduced cardiac function, increased infarct area and infiltration of inflammatory cells, decreased angiogenesis in the infarcted myocardium, and increased expression of MIF, MMP-2, and MMP-9 ( P < 0.05). Notably, Ad5-TK-1 treatment significantly improved cardiac function ( P < 0.05), markedly reduced infarct area, less inflammatory cell infiltration and elevated angiogenesis in the MI rats. The expression of MIF, MMP-2, and MMP-9 in the infarcted myocardium was decreased by Ad5-TK-1 treatment ( P < 0.05). Conclusions: TK-1 overexpression partially reverses cardiac remodeling in MI rats, and this effect is associated with downregulation of MIF, MMP-2, and MMP-9 in the myocardium.